PENERAPAN PENJAMINAN MUTU RADIOLOGI PADA KENDALI MUTU PERALATAN BUCKY GRID PESAWAT DIGITAL RADIOGRAPHY - Diana Wahyusyafitri; Gatot Murti Wibowo (Perhimpunan Radiografer Indonesia (PARI), 2018)
The research about grid performance testing in Radiology Installation RA Kartini Jepara have been done using X-ray digital radiography type Multix Select DR. X-ray digital radiography hasn’t been re-tested after acceptance testing in 2016. Based the frequency, it’s often use. The purpose of this study to know the implementation of radiology quality assurance and quality control and to determine the result testing. Research conducted in the examination room in radiology installation RA Kartini Jepara with depth interviews, two radiographers as a respondents. Then, put a Grid Allignment Test Tool in the middle of center beam, with vertical rays. Afterthat, all the holes exposed by a factor using 45 kVp and mAs setting 1 and 5. Then do the processing and measure the optical density using densitometer three times each holes. In the analysis of data from measurement should determine the value of highest density on the 3rd or center hole and getting decreases to the lateral. The result show the quality assurance and quality control aren’t going well because there is none about QA Committe. Density measurement data show, on the first hole has 2,48 and 2,56. On the second hole has 2,66 and 2,74. On the third hole has 2,71 and 2,81. On the fourth hole has 2,69 and 2,72. The fifth hole has 2,71 and 2,78. The first hole show lowest density value and getting decreases to the lateral side. It means bucky is missalignment with central rays.